Perancangan Mural sebagai Daya Tarik Wisata Alas Outbound Edukasi di Desa Simpang Kecamatan Prambon Sidoarjo - Hanafi Moeslim; Alfian Candra Ayuswantana (Institut Nalanda, 2023)
Mural has now become a common media found in public spaces. In addition to being a means of information, murals also have interesting images and can have other functions, namely as a means of conveying messages, advertising materials, propaganda materials and even educational information documents. The making of this mural design will be applied to Community Service through the Independent Lecture Competency Program (PKKM) Bina Desa held by the Visual Communication Design Education Program of the National Development University